EXPLORING THE QUALITY OF LIFE OF PARENTS AND SIBLINGS OF CHILDREN WITH CEREBRAL PALSY: IMPLICATIONS FOR CAREGIVING AND SUPPORT - KOTIYA, VIDHI; CHOUDHARY, RICHA; YADAV, ANJU (International Journal of Current Pharmaceutical Research, 2023)
Objective: This study aimed to explore the quality of life (QOL) of parents and siblings of children with cerebral palsy (CP) and its implications for caregiving and support. Methods: A hospital-based cross-sectional descriptive study was conducted in the Department of Pediatrics, S. P. M. C. H. I. Hospital, SMS Medical College, Jaipur, India, from March 2021 to December 2021. Parents and siblings of children with CP, aged 2-12 y, were enrolled. The World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire was used to assess QOL. Data analysis was performed using descriptive statistics and SPSS software. Results: The study included 100 parents and siblings of children with CP. Most children had normal birth weight and were born at term. Spastic quadriplegia was the most common type of CP observed. More than half of the children had other medical conditions, with epilepsy being the most prevalent. WHO-QOL BREF scores were low across all domains. Physical domain was the most affected (9.97±2.15), followed by Social interaction domain (10.48±2.32) and psychological domain (10.83±2.26) and Environment domain (11±2.23). The age and gender of the child, severity of disability, education of caretakers, family type, socioeconomic status, chronic illness did not significantly impact the QOL of caregivers. Caregivers with impaired functional status reported lower QOL scores. Meeting scheduled appointments positively influenced caregivers' physical and environmental domain scores. Conclusion: The caregivers of children with CP experience lower quality of life and high levels of stress. If sustained over time it can affect family dynamics and quality of care provided to such children with CP. The implications of these findings can guide the development of targeted interventions and support programs for caregivers of children with CP.